ANALISIS FILOSOFIS PEMIKIRAN EKONOMI AL-GHAZALI TENTANG KESEIMBANGAN (MIZAN) DAN KONTRIBUSINYA TERHADAP PERDEBATAN EKONOMI GLOBAL - Nurlaili Rismawati Matondang; Sarmiana Batubara (EKSYA : Jurnal Ekonomi Syariah, 2025)
This study aims to philosophically explore the concept of balance (mizan) in Al-Ghazali's economic thought, linking it to the structure of maslahah, maqasid al-shari'ah, morality, and social order, and analyze its contribution to contemporary global economic debates, particularly regarding inequality, economic crises, and equitable sustainable development. This study uses a qualitative descriptive-philosophical approach based on literature studies. The analysis is conducted using a hermeneutic and comparative approach to interpret the concept of mizan in Al-Ghazali's works, compare it with the modern global economic paradigm, and examine the relevance of this thought in the contemporary economic context. This study shows that Al-Ghazali's concept of mizan operates at three levels: individual, institutional, and state. At the individual level, mizan prioritizes balance in consumption, work, and market morals. At the institutional level, this concept is applied in markets and ethical financial institutions. At the state level, mizan includes public policies that focus on the equitable distribution of wealth and the management of public finances for the common good. Al-Ghazali's thought offers a critique of neoliberal economics and consumerism and proposes alternatives for a more ethical, sustainable economy. The implication of this research is that Al-Ghazali's economic thought makes a significant contribution to the development of a more just and sustainable global economic theory. The concept of mizan can be the basis for formulating economic policies that focus not only on material growth but also on social and spiritual well-being. The application of mizan principles in economic policy can reduce social inequality, support sustainable development, and create a more inclusive and equitable economic system.